“She Cuppeth the Lightning in her Hand”: Spirituality, Domination, and Violence in The Power (2016) by Naomi Alderman - Małgorzata Warchał (Zagadnienia Rodzajów Literackich)
The Power by Naomi Alderman offers a dystopian vision of the world in which girls and women develop the ability to produce electric current. The power is both a blessing and a curse since it enables women to stand up to oppression and upturn male dominance, but also turns their bodies into lethal weapons. The following article aims to analyse depictions of women and girls in the novel while taking into consideration their entanglement in religion, organised crime, and politics. The analysis includes two perspectives, ecofeminist and posthuman. The power, on the one hand, can be seen as an emblem of rediscovered interconnection between people and the forces of nature or animals. On the other hand, the depictions of women make them resemble cyborgs, combinations of living organisms and machines. Moreover, the article comments on the utopian potential of the world presented in the novel, and on the dystopian outcomes of the described shift of power.